Identifying the Essential Components of Designing a Self-Care application for female with Pelvic Floor Disorders - Reza Safdari; Niloofar Mohammadzadeh; Nasim Shokouhi; Azizeh Farzinmehr; Mehrshad Mokhtaran; shahrbanoo pahlevanynejad; Mahnaz Mirsane (Tehran University of Medical Sciences, 2020)
Background and Aim: Pelvic floor disorders are a common disease which, with varying degrees of severity, disrupts daily life and also decreases the quality of life of the individual. This disease can be cured by lifestyle modifications and self-care education; on the other hand, smartphones have become a good platform for health services and therapeutic interventions. The aim of this study was to identify information and educational components for the self-care application of women with pelvic floor disorders. Materials and Methods: This descriptive study was performed in Yas Hospital affiliated to Tehran University of Medical Sciences. According to Morgan table, 30 gynecologists who were randomly selected were included in the study. The data gathering tool was a researcher-made questionnaire which its validity and reliability were confirmed (α=0.85) and its content was provided by reviewing the scientific sources. Results: The results of the analyzes showed that from the experts' point of view the interventional section including reminders, daily activities diaries and targeting with an average score of 4.14 has been of great importance. Since then, the applied and self-care section with an average score of 4.364is ranked second in priority. Conclusion: According to a survey by experts who play a major role in the management of the disease. The essential components of this application were identified in three main sections consist of: electronic records, the interventional section and the practical and self-care and their subsections.